If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34(x + 2) = -1 Reorder the terms: 34(2 + x) = -1 (2 * 34 + x * 34) = -1 (68 + 34x) = -1 Solving 68 + 34x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-68' to each side of the equation. 68 + -68 + 34x = -1 + -68 Combine like terms: 68 + -68 = 0 0 + 34x = -1 + -68 34x = -1 + -68 Combine like terms: -1 + -68 = -69 34x = -69 Divide each side by '34'. x = -2.029411765 Simplifying x = -2.029411765
| 8a+6(a+7)=6(3a+7)+8 | | x+x+.56+.74=10.41 | | -3(1-8n)-8(4n-1)=61 | | 3x^2-15+x^2+x=90 | | b=65(10+9)w | | 11/14-2/10 | | 6z(z^2-1)=0 | | b=65(10+9) | | 10=1.25x | | 5(x-2)-4x=6+3x | | -3t+7u= | | 9n-9=-90 | | 0=6/7y | | .5x+5=6x+20 | | 8(7-4v)-8=-208 | | -6-(-3)=3 | | 5x+18=2(2x+5) | | 3x-9=2x+12 | | 24x-36=-6x+24 | | 6w+4=2-5(3w-1) | | 11-2b=-7-5b | | 7(16x-6)=8(21x-5) | | 2-2n+8n=20 | | x-10+x=-16 | | -2+6x=16x+8 | | j=g(1+rt) | | j=g | | n=-9+33 | | 2x-3+x+2x-3+x= | | 18/x=-2 | | n/8=-3/8 | | x-3/8=7/12 |